Extracellular DNA in monochloraminated drinking water and its influence on DNA-based profiling of a microbial community - Sakcham, Bairoliya (2021)
The interaction between biofilms and disinfectant in drinking water distribution systems (DWDS) as well as the role of this interaction in the formation of disinfection byproducts has been extensively studied in recent years. In contrast, lysis of cells and/or release of intracellular biomolecules from inactivated/damaged cells and their fate and implications are an overlooked aspect of DWDS. In particular, DNA, once released into DWDS, may persist in water as extracellular DNA (eDNA). In this study, we report for the first time that the total DNA extracted from monochloraminated drinking water contains a high fraction of eDNA. Drinking water samples were obtained from locations 1 (~20-year-old pipeline) and 2 (~7-year-old pipeline) using glass fiber membranes with a nominal pore size of 0.4 μm. At location 1, 85-386 ng of eDNA was found per liter of sampled water, which accounted for 52 ± 12% of total DNA, while at location 2, 33-58 ng of eDNA was found per liter of sampled water, accounting for 42 ± 8% of the total DNA. We further showed that the removal of eDNA reduced α diversity, increased community evenness, and changed the relative abundance of detected taxa. Our findings lead to future research questions about the source, fate, and implications of eDNA in DWDS.